The SABER School Feeding policy tool: a 10-year analysis of its use by countries in developing policies for their national school meals programs - Schultz, Linda; Renaud, Alice; Bundy, Donald A. P.; Barry, Fatoumata B. M.; Benveniste, Luis; Burbano de Lara, Carmen; Lo, Mouhamadou Moustapha; Neitzel, Jutta; O’Grady, Niamh; Drake, Lesley (Frontiers in Public Health, 2024)
Since its launch in 2011, 59 governments have used the World Bank’s Systems Approach for Better Education Results (SABER) policy tool to design their national school-based health and nutrition programs. This tool guides governments to self-evaluate their education system policies against international benchmarks and identify actionable priorities to strengthen national programs. Thirty-two of the 49 countries in sub-Saharan Africa (65%) have undertaken a SABER review, and globally the approach has been adopted by 68% of the world’s low-income countries and 54% of lower-middle-income countries. Analysis of 51 comparable SABER School Feeding surveys suggests that countries with longer established national school meals frameworks tend also to be more advanced in other policy areas, and vice versa. The SABER reviews consistently identify, perhaps predictably, that the weakest policy areas relate to program design, implementation and fiscal space. This analysis also found that the tool had an additional value in tracking the evolution of policies when implemented over several time points, and showed that policy areas become more advanced as national programs mature. These benefits of the tool are particularly relevant to the 98 countries that co-created the global School Meals Coalition in 2021. The Coalition member countries have the specific goal of enhancing coverage and support for the well-being of schoolchildren and adolescents affected by the school closures during the COVID-19 pandemic. The SABER tool has the demonstrated potential to implement, accelerate and track changes in school meals policy and, since it has been previously used by 74% (31/42) of low- and lower-middle-income countries in sub-Saharan Africa, is an already accepted element of the political economies of those countries and so has the potential to be deployed rapidly.